Whole-genome resequencing of large yellow croaker (Larimichthys crocea) reveals the population structure and signatures of environmental adaptation - Tetsuo Kon (Nature Portfolio, 2021)
Abstract Large yellow croaker is an economically important fish in China and East Asia. Despite its economic importance, genome-wide adaptions of domesticated large yellow croaker are largely unknown. Here, we performed whole-genome resequencing of 198 individuals of large yellow croaker obtained in the sea or from farmers in Zhoushan or Ningde. Population genomics analyses revealed the genetic population structure of our samples, reflecting the living environment. Each effective population size is estimated to be declining over generations. Moreover, we identified genetically differentiated genomic regions between the sea-captured population in the Zhoushan Sea area and that of the Ningde Sea area or between the sea-captured population and the farmed population in either area. Gene ontology analyses revealed the gene groups under selective sweep for the adaptation to the domesticated environment. All these results suggest that individuals of the large yellow croaker populations show genomic signatures of adaptation to different living environments.